الحصانة الدبلوماسية في القانون الدولي من منظور الشريعة: دراسة مقارنة للمواد المتعلقة بالحصانة الدبلوماسية في إتفاقية فيينا 1961م - سيسي، فهد بن محمود (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2017)
The study aims to focus on the immunities of a diplomatic representative in Islamic Law and international law depicted by the Vienna Convention on Diplomatic Relations of 1961. The study covers the most important features of this immunity and aspects of the agreement. It also analyses the similarities and differences between Islamic law and international law in the treatment of diplomats and the protection of their rights. Moreover the study assesses the most prominent sources of law relied upon by both Islamic jurisprudence and international law in the origination of principles and foundations that grant diplomats immunity. In addition, a review of some contemporary issues in diplomacy is conducted to examine the comprehensiveness of the Vienna Convention on Diplomatic Relations in 1961 in dealing with them and providing solutions. A comparison to the Islamic Jurisprudence approach will then be made based on its maxims and divine revelation pertaining to Islamic Political Science.